INTEGRATION OF LEADERSHIP TRAINING IN THE MEDICAL AND HEALTH PROFESSION EDUCATION CURRICULA - Ekayani, Ni Wayan Diana; Findyartini, Ardi; Anugrapaksi, Eghar; Nadarajah, Vishna Devi V. (Universitas Gadjah Mada, 2023)
Background: Leadership is a crucial competency for health professions to collaborate and improve health services. Health profession schools should facilitate students in developing leadership competency to prepare them for their duties in the future.Gaps: Indonesia has complex health problems, high-power distance, and collectivist culture. Leadership training in Indonesia has not been widely reported. The tight curriculum, lack of students' awareness about the importance of leadership competency, and students who focus on improving knowledge and skills about their profession are challenges in integrating leadership into formal education.Recommendation: Health profession schools should identify the needs and domain of leadership competency in the respective profession. We should also identify opportunities to integrate leadership into the curricula. Integration of the leadership program should be conducted longitudinally, all along with the curricula. Preparation of learning methods, systematic assessment, and faculty development should be considered. Last, students must be involved and supported in every activity to make them engage with the program and learn best.